HF messaging system with automatic link establishment (ALE) capability - Hasan, Nurulfadzilah (2006)
HF radio spectrum, ranging from 3 to 30 MHz can be utilized for voice and data communication. One of the benefit of using HF for communicating is that HF system is low-cost, requires minimum equipments and easy to set up. But due to the unpredictability and propagation problems such as multipath fading, interference and attenuation, communication using HF becomes very challenging. Besides, the availability of the channels varies depending on the time of day, seasons and the condition of the ionosphere. The purpose of this research is to design a HF messaging system equipped with Automatic Link Establishment (ALE) capability. ALE is an adaptive radio technology for automatically establishing communications over HF single sideband (SSB) links using the best frequency possible. The objective of the research is to design a messaging system that permits reliable data transmission over the HF radio with minimum cost and equipments. This research also looked at the feasibility of implementing ALE as software, designed using Visual C++ programming language. Equipments used in this research are commercial HF radio and modem, which are both controlled by the software. Field testing is conducted between UTM Skudai and several places in Malaysia to verify the performance of the system. From the results, it is proven that by applying adaptive radio technology, propagation problems can be overcome and reliability of data transmission can be improved. Moreover, amateur radio users can use the system, as it requires minimum equipment.